Статус побутової речі в сучасній культурі: культурологічний аспект. - Бондарук, М. О.; Bondarchuk, M. O. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Статтю присвячено проблемі визначення культурного статусу сучасної побутової речі. З’ясовано смислові рівні її побутування та зміну параметрів функціонування. Проаналізовано основні типи ставлення людини до речі та їх історичну трансформацію. У контексті пошуків причин девальвації статусу речі в сучасній культурі досліджено вплив реклами на смислові параметри побутової речі, а також визначено специфіку процесу її розречевлення сьогодні.The status of the common object in modern culture: culturological aspect. The article is devoted to the problem of definition of the cultural status of the common object of contemporaneity. The semantic levels of it’s location in life and measuring of the parameters of it’s functioning is founding out. The primary type of the human attitude to the common object and their historical transformation is analyzing. In the context of the searching of the motives of devaluation of the object status in the modern culture the dominancy of the advertising on the semantic parameters of the common object, as well as the specific of the process of the waiting of corporality is investigating. Also proposed classification of the main types of cultural system «human – thing» according to the nature of their comunications. The author defines the prospects of development of the relationship between man and things in modern culture.
Status Household Things in Contemporary Culture: Cultural Aspect.
Keywords: річ; object; предметне середовище; subject environment; гаджет; concern; дизайн; design; кіч; kitsch; культура; culture; споживацтво; consumerism; реклама; advertising